Faculty and resident perspectives on ambulatory care education: A collective case study of family medicine, psychiatry, and surgery - Veinot, Paula; Lin, William; Woods, Nicole; Ng, Stella (Canadian Medical Education Journal, 2017)
Background: Ambulatory care (AC) experiences within medical education are garnering increasing attention. We sought to understand how faculty and residents’ describe their experiences of AC and ambulatory care education (ACEduc) within, between, and across disciplinary contexts. Methods: We designed a Stakian collective case study, applying constructivist grounded theory analytic methods. Using purposive and snowball sampling, we interviewed 17 faculty and residents across three instrumental cases: family medicine, psychiatry, surgery. Through constant comparative analysis, we identified patterns within, between, and across cases. Results: Family medicine and psychiatry saw AC as an inherent part of continuous, longitudinal care; surgery equated AC with episodic experiences in clinic, differentiating it from operating. Across cases, faculty and residents cautiously valued ACEduc, and in particular, considered it important to develop non-medical expert competencies (e.g., communication). However, surgery residents described AC and ACEduc as less interesting and a lower priority than operating. Educational structures mediated these views. Conclusion: Differences between cases highlight a need for further study, as universal assumptions about ACEduc’s purposes and approaches may need to be tempered by situated, contextually-rich perspectives. How disciplinary culture, program structure, and systemic structure influence ACEduc warrant further consideration as does the educational potential for explicitly framing learners’ perspectives.